1988
DOI: 10.1161/01.str.19.11.1383
|View full text |Cite
|
Sign up to set email alerts
|

Global cerebral ischemia and intracellular pH during hyperglycemia and hypoglycemia in cats.

Abstract: In 27 cats treated to vary arterial serum glucose concentrations, we measured cerebral highenergy phosphate metabolite concentration and intracellular pH using in vivo phosphorus-31 nuclear magnetic resonance spectroscopy during transient global cerebral ischemia and reperfusion. Hypoglycemia was induced with 4 units/kg i.v. insulin in six cats before ischemia; hyperglycemia was induced with 1.5 g/kg i.v. glucose in six cats before and in six cats during ischemia. Nine untreated cats subjected to ischemia with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Hyperglycemic-induced cerebral acidosis is generally considered the mechanism for enhanced brain injury (Chopp et al, 1988;Li and Siesjo, 1997), with most interest focused on injury to neurons and astrocytes. However, blood-brain barrier (BBB) opening during reperfusion is exacerbated by severe HG (Dietrich et al, 1993;Ginsberg et al, 1980;Siemkowicz, 1981) and can result in hemorrhagic conversion of the infarct (de Courten-Myers et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemic-induced cerebral acidosis is generally considered the mechanism for enhanced brain injury (Chopp et al, 1988;Li and Siesjo, 1997), with most interest focused on injury to neurons and astrocytes. However, blood-brain barrier (BBB) opening during reperfusion is exacerbated by severe HG (Dietrich et al, 1993;Ginsberg et al, 1980;Siemkowicz, 1981) and can result in hemorrhagic conversion of the infarct (de Courten-Myers et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas ischemic brain tissue typically reaches a pH, of 6.5-6.8, coincident hyperglycemia can drive interstitial pH down to 6.0 (Siemkowicz and Hansen, 1981;Kraig et al, 1985). Intracellular acidosis during ischemia is also exacerbated by hyperglycemia (Chopp et al, 1988;Hope et al, 1988; Widmer et al, 1992) and, at least in glia, reaches levels (pHi 5 5.5) capable of killing these cells directly (Walz and Wuttge, 1989; Kraig and Cheder, 1990). Direct pHi measurements in neuronal cells during hyperglycemic ischemia have not been reported, though Plum (1 983) has suggested that ischemic neurons equilibrate with their acidotic environment.…”
mentioning
confidence: 99%
“…8,45 In cats made hypoglycemic before ischemia, the observed reduction in pH i was attenuated both during ischemia and early during reperfusion. The observation, during occlusion, of a pH i response to hypoglycemia in that study suggests that ischemia was incomplete because energy metabolism responded to manipulation of serum glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia has been shown to increase ischemic lactic acidosis 1 and cellular damage experimentally [2][3][4][5][6] and clinically, 7 whereas hypoglycemic animals have less acidosis than those studied under normoglycemic and hyperglycemic conditions. [8][9][10] However, potentially protective effects of insulin-induced hypoglycemia on energy metabolism and outcome are not consistently observed. 1,[11][12][13][14][15][16][17][18] For example, rats made hypoglycemic by insulin injection before regional ischemia was induced by middle cerebral artery occlusion had smaller infarcts than normoglycemic controls, 19 and chronically hyperglycemic diabetic rats had even larger infarct volumes.…”
Section: Introductionmentioning
confidence: 99%